Effect of Light Emission Through an Optical Fiber Device on the Bond Strength of a Hollow Experimental Intraradicular Post - Inagati, Cristiane Mayumi [UNESP]; Grangeiro, Manassés Tercio Vieira [UNESP]; Rossi, Natália Rivoli [UNESP]; bst, João Paulo Mendes Tr; Nakano, Leonardo Jiro Nomura [UNESP]; de Carvalho, Paula Carolina Komori [UNESP]; de Arruda Paes, Tarcisio José [UNESP] (My University, 2022)
Purpose: To evaluate the effect of irradiation with an optical-fiber device on the bond strength of hollow and partially opaque intraradicular posts. Materials and Methods: An optical-fiber accessory tip was attached to a light-curing unit to emit light through the central hollow of an experimental fiberglass post. The samples were divided into 4 groups (n=80) according to the protocol (Variolink N [light cured] or Multilink N [dual-curing luting material]) and the light-curing mode (performed con ventionally or with the optical fiber): GF: light-curing luting material; GFF: light-curing luting material and optical fiber; GD: dual-curing luting material; GDF: dual-curing luting material and optical fiber. The samples were tested immedi ately or after aging. Push-out bond strength, failure mode, degree of conversion (DC, assessed at the peak of 1750cm-1), and stress distribution by finite element analysis were performed. Quantitative data were analyzed using 3-way ANOVA (luting material x light curing x depth) and 2-way ANOVA (aging x luting material), followed by Tukey’s test. Results Bond strength was significantly affected by the luting material protocol (p<0.001), depth (p=0.010), and light curing mode (p= 0.031). The GFF group revealed higher bond strength in the middle and apical portions. The most frequent failure modes were adhesive in the apical portion for the GFF and GDF groups. The DC was higher for GF and GFF groups. Conclusion: Using the optical-fiber device led to superior bond strength results when a dual-curing luting material was used
Keywords: Dental posts; Finite element analysis; Light-curing of dental adhesives; Luting; Optical fiber